Pengembangan Aplikasi Media Komunikasi Badan Pengawas Pemilu Republik Indonesia Berbasiskan Web dan Wap - Alex Chandra; Tonny Lion Kencana; Yurri Kurnianingsi; Elidjen Elidjen (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The research objective is to develop Web-based and WAP-based communiaction media applications to facilitate communication between the Board of Election Supervisors of Republic of Indonesia (Bawaslu RI) with all stakeholders associated with the public election. The research method used are analysis and design Methods. Analysis includes system analysis, identification of information needs, and the analysis of existing websites. The results of this analysis are used to design the applications of the proposed system of communication media. The design is implemented for database design and structured web-based and WAP-based applications. This research obtains Web-based and WAP-based communiaction media applications that facilitate communication about everything related to the public election.